Le multimédia face à l’immédiat - Amandine Degand (Communication)
Online journalists lack the time to crosscheck their information before publication. This conclusion comes from 56 days of on-site observation in 11 Belgian newsrooms. In a comprehensive approach, this article addresses the issue of immediacy and its implications. It appears that the balance between the journalistic values of immediacy and reliability is disrupted. This in turn introduces, in today’s journalistic practices, an uncertainty that journalists only partially handle, through temporary arrangements.